2017
DOI: 10.1152/ajprenal.00420.2016
|View full text |Cite
|
Sign up to set email alerts
|

ENaC and ROMK activity are inhibited in the DCT2/CNT of TgWnk4PHAII mice

Abstract: Mice transgenic for genomic segments harboring PHAII (pseudohypoaldosteronism type II) mutant Wnk4 (with-No-Lysine kinase 4) (TgWnk4) have hyperkalemia which is currently believed to be the result of high activity of Na-Cl cotransporter (NCC). This leads to decreasing Na delivery to the distal nephron segment including late distal convoluted tubule (DCT) and connecting tubule (CNT). Since epithelial Na channel (ENaC) and renal outer medullary K channel (ROMK or Kir4.1) are expressed in the late DCT and play an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…We observed an increase in CCD mass that is paralleled by an increase in pendrin activity with only a modest decrease in CNT mass (CNT fractional volumes were 5.16% AE 0.54% vs. 3.41% AE 0.36% of kidney cortex in control and TgWnk4 PHAII mice, respectively (n ¼ 4 for each group, P ¼ 0.036), which likely explains the decrease in ENaC and ROMK currents seen in the DCT2/early CNT of TgWnk4 PHAII mice. 34 However, the observation that pendrin deletion normalized blood K þ concentration in TgWnk4 PHAII mice indicates that remodeling of the CNT is not the primary cause of K þ retention in our model. In summary, both models (CA-SPAK and WNK4-PHAII) are characterized by the combination of NCC activation along with a second mechanism that differs from a model to another but that results ultimately in a decrease in K þ secretion.…”
Section: B-ics Exchange Hcomentioning
confidence: 70%
“…We observed an increase in CCD mass that is paralleled by an increase in pendrin activity with only a modest decrease in CNT mass (CNT fractional volumes were 5.16% AE 0.54% vs. 3.41% AE 0.36% of kidney cortex in control and TgWnk4 PHAII mice, respectively (n ¼ 4 for each group, P ¼ 0.036), which likely explains the decrease in ENaC and ROMK currents seen in the DCT2/early CNT of TgWnk4 PHAII mice. 34 However, the observation that pendrin deletion normalized blood K þ concentration in TgWnk4 PHAII mice indicates that remodeling of the CNT is not the primary cause of K þ retention in our model. In summary, both models (CA-SPAK and WNK4-PHAII) are characterized by the combination of NCC activation along with a second mechanism that differs from a model to another but that results ultimately in a decrease in K þ secretion.…”
Section: B-ics Exchange Hcomentioning
confidence: 70%
“…Altered regulation of ROMK and ENaC has been reported, but the phenotypes are surprisingly divergent manners depending on the WNK FFHt model. Recently, Zhang and coworkers 51 found that ROMK and ENaC activities are suppressed in the late DCT/early CNT of mice transgenic for WNK4 FFHt, identical to CA-SPAK mice. By contrast, WNK4 FFHt mice were reported to have increased ENaC activity and no change in ROMK protein abundance, although ROMK was misidentified with a nonspecific antibody.…”
Section: Discussionmentioning
confidence: 94%
“…We demonstrated previously that the basolateral Kir4.1 activity is closely related to the NCC activity in the DCT because deletion of Kir4.1 reduced NCC expression and function [22]. In contrast, the basolateral K + channel activity in the DCT in NCC null mice (Wang’s unpublished observation) or in Wnk4 PHAII transgenic mice with high NCC was similar to WT mice[43]. Here, we show that Kir4.1 activity plays a key role in mediating the effect of dietary K + intake on NCC activity, because the effect of dietary K + intake on NCC activity is completely absent in KS-Kir4.1 KO mice.…”
Section: Discussionmentioning
confidence: 99%